IMPLEMENTASI SISTEM PRESENSI KARYAWAN BERBASIS IOT DAN WEBSITE DI PT TANJUNG ENIM LESTARI DENGAN TEKNOLOGI RFID DAN KAMERA - Mgs Ilham Zuhdi; Tata Sutabri (ADISAM PUBLISHER, 2025)
Attendance recording is an essential part of employee management and reporting in institutions or companies. However, many companies still rely on manual attendance systems, where employees fill out printed attendance sheets. This method often leads to problems, such as damage or loss of the sheets, requiring reprinting and re-entering data, which is time-consuming and inefficient. To address these issues, a modern attendance system was developed using Internet of Things (IoT) technology. This system incorporates the ESP8266 module for connectivity, RFID for employee data scanning, and the ESP32 Cam for facial validation. Additionally, the system integrates with a web-based interface for efficient data management and reporting. The proposed solution aims to simplify the attendance process, reduce errors, and enhance reliability compared to traditional manual systems. By leveraging IoT and website technology, this system provides a more eflective and sustainable approach to managing employee attendance in organizations